Structural and morphologies of (1-x)BaTiO3-xBaFe 0.5Nb0.5O3 solid solution - S. Eitssayeam (2018)
The structural and physical properties of(l-x)BaTiO3 -xBaFe 0.5Nb0.5O3 ceramics system were investigated as a function of the BaFe0.5Nb0.5O3 content by X-ray diffraction (XRD) and dielectric measurement technique. Studies were performed on the samples prepared by solid state reaction for x = 0, 0.2, 0.4 and 0.6. The XRD analysis demonstrated that with increasing BFN content in (l-x)BT-xBFN, the structural change occurred from the tetragonal to the cubic phase at room temperature. Changes in the morphology were then related to these structural depending on the BFN content. © 2008 Trans Tech Publications, Switzerland.